PERAN BALAI BESAR PENGAWAS OBAT DAN MAKANAN DALAM PENCEGAHAN PELAKU USAHA YANG MENDISTRIBUSIKAN KOSMETIK ILEGAL - Nur Khalifatunnisa; Fatah Hidayat (Tazir, 2021)
Center for Food and Drug Supervisory Agency (BBPOM) is an agency authorized to supervise and overcome the circulation of drugs and food under the auspices of the Food and Drug Supervisory Agency (BPOM), the government to protect and strive for the free circulation of cosmetics in the community. The problem of distributing illegal cosmetics that do not meet quality standards is suspected to still occur in the city of Palembang even though it has been investigated and supervised by the Food and Drug Supervisory Center in Palembang, this is because there are no penalties that provide a deterrent effect to business actors. The writing method used in this study uses a qualitative descriptive method. While the method of data collection using interviews, observation and documentation. The results of the study can be concluded, that there are business actors who distribute illegal cosmetics among the people in the city of Palembang. socialization and law enforcement. And if viewed in Islamic criminal law, the role of the drug and food supervisory center in Palembang has carried out in accordance with the teachings of Islamic law for business actors who violate the rules in Islamic criminal law called punishment ta'zir. Keywords: Balai Besar POM, Business Actor, Illegal Cosmetics